Telemedicine use in current urologic oncology clinical practice - Paesano, Nahuel; Carrion, Diego M.; Autrán Gomez, Ana María (Frontiers in Surgery, 2022)
Introduction In the last fifteen years, there have been important technological advances in telehealth systems and urology, along with other specialties, has been a pioneer in the successful use of this medical care modality. Due to the COVID-19 pandemic, the use of telemedicine has been rapidly embraced by the urology community around the world. A review of the most relevant and updated articles on telemedicine and telehealth in urology has been carried out with the aim of better understanding how it has been implemented to date, as well as reviewing concepts, current regulations, health policies and recommendations for its implementation. Methods A narrative review of the current literature published up to April 2022 on the use of telemedicine in urology was performed. From the search results, 42 publications were obtained for analysis. Results Telemedicine in urology has been shown to be useful in a variety of clinical scenarios within urological practice, from benign diseases to advanced cancers. This is due to the positive impact on medical consultation times, lower patient mobility costs, less work absenteeism and greater protection for both the patient and the doctor. The main limitations for the use of telemedicine lie in the impossibility of a correct physical examination, which is essential in certain situations, as well as the lack of accessibility to technology in disadvantaged populations and in elderly patients who have not adapted to the use of technology, as well as the lack of development of health policies to establish their implementation in some countries. Conclusion Telemedicine is in full growth. There is much information in the current literature on the successful adoption of telemedicine for patients suffering from urological diseases. While the use and implementation of these new practices has been rapid in the urology community, more work is needed to bring more accessible specialty care to underserved and underdeveloped areas. Health policies must promote its development to reduce costs and increase access.